Pancytopenia and Progressive Splenomegaly in Patient with Disseminated Histoplasmosis - Paulus Budiono Notopuro; Arifoel Hajat; Made Putra Sedana (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Disseminated histoplasmosis is a severe manifestation of fungal infection caused by Histoplasma capsulatum. It usuallyoccurs in a patient with an immunodeficiency state. With the increase of HIV infection and the use of immunosuppressantdrugs lately, its prevalence also increases. A case of 43 years old female with prolonged fever, pancytopenia, and massiveprogressive splenomegaly. The diagnosis of disseminated histoplasmosis and the secondary hemophagocytic syndromewas made based on bone marrow examination that showed increased hemophagocytic processes and multipleintracytoplasmic H.capsulatum. She had been treated with Itraconazole 200 mg for three months. In the first month'sevaluation, her complete blood count improved without any transfusions, and the size of her spleen size decreased. She hadbeen fully recovered after the completion of 3-month treatment.